DER ( Debt to Equity Ratio) dalam sorotan: Mengukur kekuatan permodalan Bank Syariah Indonesia (BSI) selama 2020-2024 - Hidayah, Anadia Hidayah (Maliki Interdisciplinary Journal, 2025)
This study aims to evaluate the solvency ratio as one of the indicators of financial health at Bank Syariah Indonesia (BSI) during the period of 2020–2024. The analysis focuses on the Debt to Equity Ratio (DER) as the main ratio that illustrates the comparison between total debt and shareholders’ equity. This research employs a descriptive quantitative method based on the published annual financial statements of BSI. The results indicate that in 2020–2021, the DER remained at a low level, reflecting a strong capital structure. However, from 2022 to 2024, the DER increased significantly, suggesting a higher reliance on debt financing and an escalation in leverage risk. These findings provide an overview of BSI’s solvency position and serve as a basis for improving capital structure management in the future. Moreover, this study is expected to contribute to the development of Islamic financial management theory and provide valuable information for stakeholders such as investors, management, and regulators.